# If one root of a

Since -5 is the zero of the first equation,

Put x = -5 in first equation

2(-5)2 + p (-5) – 15 = 0

2× 25 – 5p – 15 = 0

5p = 50 – 15

5p = 35

p = 7

If the roots are equal, then

b2 – 4ac = 0

When we compare the above quadratic equation with the generalized one we get,

ax2 + bx + c = 0

a = p = 7

b = p = 7

c = k

(7)2 – (4 × 7 × k) = 0

(7)2 – 28 k = 0

28k = 49

k = 49 / 28

k = 7 / 4

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

If u(x) = (x – 1)Rajasthan Board Mathematics

Find the lowest cRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

The area of a recRajasthan Board Mathematics

The LCM and HCF oRajasthan Board Mathematics

If α and β are thRajasthan Board Mathematics

Find the zeroes oRajasthan Board Mathematics

Write ShridharachRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics